2015
DOI: 10.3201/eid2105.142011
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofOnchocerca lupiin Dogs and Black Flies, California, USA

Abstract: We implicated the black fly as a vector for this filarial zoonotic parasitic infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…are typically parasites of ungulates, with the notable exception of O. volvulus , which parasitizes humans. Most cases of canine onchocercosis diagnosed in the United States have been found in dogs from the southwestern United States or California …”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…are typically parasites of ungulates, with the notable exception of O. volvulus , which parasitizes humans. Most cases of canine onchocercosis diagnosed in the United States have been found in dogs from the southwestern United States or California …”
Section: Introductionmentioning
confidence: 88%
“…Infective larvae are transmitted when the insect vector again feeds upon the host and the larvae mature into adult worms, mate, and release microfilariae within the definitive host. The black fly, Simulium tribulatum , was recently identified as a putative insect vector of O. lupi in California (USA) . Ongoing work also suggests black flies as the putative vector in Albuquerque, New Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, the vectors of O. volvulus are primarily members of the Simulium damnosum Theobold species complex, whereas in Latin America, a number of Simulium species serve as vectors of O. volvulus (World Health Organization, 1995). More recently, it has been reported that sequences identical to Onchocerca lupi Rodonaja, 1967 have been detected in Similium tribulatum Lugger collected in southern California, implicating S. tribulatum as a potential vector for O. lupi in this region (Hassan et al ., ). Simulium tribulatum is a member of the S. vittatum species complex (Adler et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…act as vectors for other Onchocerca species, their role as vectors for O. lupi remains unknown. Nevertheless, O. lupi DNA has recently been detected in the black fly Simulium tribulatum in the USA [14]. Clinical manifestations of canine ocular onchocercosis range from no apparent clinical signs to blindness [1,10].…”
Section: Discussionmentioning
confidence: 99%